SUCCESSFUL CHEMOTHERAPY ADMINISTRATION DESPITE HYPERSPLENISM AND PANCYTOPENIA: A CASE OF METASTATIC RECTAL ADENOCARCINOMA - Adil Uğur Kaan Güngör; Abdurrahman Aykut; Berksoy Sahin; Hatice Asoğlu Rüzgar (Hematology, Transfusion and Cell Therapy)
Introduction: Cytopenias in oncology patients present a significant barrier to the administration of chemotherapy. Hypersplenism is one of the leading causes of cytopenia. In this case report, we aim to present a patient diagnosed with metastatic rectal adenocarcinoma, who developed hypersplenism due to liver metastasis and was successfully treated with chemotherapy despite the cytopenias. Case Report: In September 2023, a 42-year-old female patient was diagnosed with rectal adenocarcinoma with liver metastasis. Genetic analysis revealed K-Ras, N-Ras, and BRAF mutant/wild type, MSI stable, and Her2 negative. The patient received 3 cycles of FOLFIRINOX chemotherapy. During follow-up, her hemogram results were as follows: hemoglobin: 8.6 g/dL, platelets: 26 × 10³/µL, leukocytes: 0.81 × 10³/µL, and neutrophils: 0.37 × 10³/µL. PET-CT evaluation showed regression in the metastatic lesions and newly developed splenomegaly (spleen size: 18 cm). The tumor board assessed the resectability of liver metastases, but surgery was not considered due to the anticipated insufficient remnant liver function, and local ablative therapy was administered. Arterial and venous portal ultrasonography performed to investigate the etiology of the splenomegaly showed normal findings, and no focal lesion was detected in the spleen. No infectious pathology was identified as a cause of the splenomegaly. The cytopenia was attributed to hypersplenism secondary to liver metastasis of rectal cancer. The patient was subsequently treated with 3 additional cycles of FOLFIRINOX and 11 cycles of FOLFOX combined with Bevacizumab. Granulocyte colony-stimulating factor was not administered during the treatment process. The patient remains under oncological follow-up, and chemotherapy treatment is ongoing. Conclusion: Splenomegaly and hypersplenism are important causes of pancytopenia. Our clinical experience demonstrated that chemotherapy did not exacerbate cytopenias in a patient with metastatic rectal adenocarcinoma who developed hypersplenism and pancytopenia. We have shown that with close monitoring and supportive care, chemotherapy can be safely administered in patients with pancytopenia due to hypersplenism.